Enhancing Productivity and Improving Nutritional Quality of Subtropical and Temperate Leafy Vegetables in Tropical Greenhouses and Indoor Farming Systems - Jie He (Horticulturae, 2024)
The total land used for land-based food farms is less than 1% in Singapore. As a result, more than 90% of Singapore’s food needs are imported. To strengthen food security, Singapore has set a target to develop the capability and capacity of the agri-food industry to locally produce 30% of its nutritional needs by 2030. To achieve this goal, technology is the key to helping farms to “grow more with less”. This review first discusses how aeroponic systems have been adapted for growing all kinds of leafy vegetables in the tropics through the manipulation of root-zone temperature and heat priming to save power energy. Growing vegetable crops indoors and in greenhouses not only allows the growers to achieve high productivity but also enables them to enhance nutritional values. The second part of this paper emphasizes how to achieve substantial yield through deficit irrigation with higher nutritional quality in a cost-effective manner. Growing crops vertically has become increasingly popular, as it increases land use. We establish a commercially viable LED-integrated aeroponic system to grow vegetables vertically. The last part of the paper discusses the impacts of LED spectral quality, quantity, and duration on vegetable production.